Assessment of volemia status using ultrasound examination of the inferior vena cava and spectroscopic bioimpedance in hemodialysis patients - Lazarević, Tatjana; Petrović, Dejan; Novković, Ljiljana; Janićijević, Katarina; Janićijević Petrović, Mirjana A.; Vujić, Ana; Ljujić, Biljana; Sazdanović, Maja; Kovačević, Zoran (Vojnosanitetski pregled, 2022)
Background/Aim. Hypervolemia is an important risk factor for the development of cardiovascular morbidity and mortality in patients treated with regular hemodialysis. There is still no reliable method for assessing the status of volemia in these patients. The aim of the study was to assess the status of volemia in patients treated with regular hemodialysis by measuring the parameters of the inferior vena cava (IVC) and bioimpedance. Methods. The effect of hemodialysis treatment on ultrasound parameters of the IVC, as well as on the parameters measured by bioimpedance, was examined before and after hemodialysis. The values of the N-terminal prohormone of brain natriuretic peptide (NT-proBNP) were measured both before and after hemodialysis. Forty-five patients were involved in this non-interventional cross-section study, including the patients treated with standard bicarbonate dialysis. According to the interdialytic yield, the patients were divided into three groups: I (up to 2,000 mL), II (2,000–3,000 mL), and III (over 3,000 mL). Results. The values of the IVC parameters and the parameters measured with bioimpedance were significantly lower after treatment with hemodialysis (p < 0.005). The third group of patients had a significantly higher total fluid volume in the body compared to the group I, as well as a significantly greater volume of extracellular fluid (p < 0.005). The significantly lower values of NT-proBNP in all groups (p < 0.005) were detected after hemodialysis. After treatment with hemodialysis, a positive correlation was observed between the concentration of NT-proBNP in the serum and the extracellular/intracellular water ratio. However, the correlation between NT-proBNP concentration and total fluid measured by bioimpedance spectroscopy did not reach statistical significance. Conclusion. Measurement of the IVC ultrasound parameters and volemia parameters using bioimpedance significantly contributes to the assessment of the status of volemia. Nevertheless, it cannot be used as a separate parameter, only in combination with all other methods.